Regulation of Blood Pressure by Targeting CaV1.2-Galectin-1 Protein Interaction. Issue 14 (2nd October 2018) - Hu, Zhenyu; Li, Guang; Wang, Jiong-Wei; Chong, Suet Yen; Yu, Dejie; Wang, Xiaoyuan; Soon, Jia Lin; Liang, Mui Cheng; Wong, Yuk Peng; Huang, Na; Colecraft, Henry M.; Liao, Ping; et al.
Abstract : Background: L-type CaV 1.2 channels play crucial roles in the regulation of blood pressure. Galectin-1 (Gal-1) has been reported to bind to the I-II loop of CaV 1.2 channels to reduce their current density. However, the mechanistic understanding for the downregulation of CaV 1.2 channels by Gal-1 and whether Gal-1 plays a direct role in blood pressure regulation remain unclear. Methods: In vitro experiments involving coimmunoprecipitation, Western blot, patch-clamp recordings, immunohistochemistry, and pressure myography were used to evaluate the molecular mechanisms by which Gal-1 downregulates CaV 1.2 channel in transfected, human embryonic kidney 293 cells, smooth muscle cells, arteries from Lgasl1 −/− mice, rat, and human patients. In vivo experiments involving the delivery of Tat-e9c peptide and AAV5-Gal-1 into rats were performed to investigate the effect of targeting CaV 1.2-Gal-1 interaction on blood pressure monitored by tail-cuff or telemetry methods. Results: Our study reveals that Gal-1 is a key regulator for proteasomal degradation of CaV 1.2 channels. Gal-1 competed allosterically with the CaV β subunit for binding to the I-II loop of the CaV 1.2 channel. This competitive disruption of CaV β binding led to CaV 1.2 degradation by exposing the channels to polyubiquitination. It is notable that we demonstrated that the inverse relationship of reduced Gal-1 and increased CaV 1.2 protein levels in arteries was associated with hypertension in hypertensive rats and patients, and Gal-1 deficiency induces higher blood pressure in mice because of the upregulated CaV 1.2 protein level in arteries. To directly regulate blood pressure by targeting the CaV 1.2-Gal-1 interaction, we administered Tat-e9c, a peptide that competed for binding of Gal-1 by a miniosmotic pump, and this specific disruption of CaV 1.2-Gal-1 coupling increased smooth muscle CaV 1.2 currents, induced larger arterial contraction, and caused hypertension in rats. In contrasting experiments, overexpression of Gal-1 in smooth muscle by a single bolus of AAV5-Gal-1 significantly reduced blood pressure in spontaneously hypertensive rats. Conclusions: We have defined molecularly that Gal-1 promotes CaV 1.2 degradation by replacing CaV β and thereby exposing specific lysines for polyubiquitination and by masking I-II loop endoplasmic reticulum export signals. This mechanistic understanding provided the basis for targeting CaV 1.2-Gal-1 interaction to demonstrate clearly the modulatory role that Gal-1 plays in regulating blood pressure, and offering a potential approach for therapeutic management of hypertension. Abstract : Supplemental Digital Content is available in the text.